Peran Manajemen Syariah dalam Pengelolaan dan Pengembangan Badan Usaha Milik Pondok Pesantren (BUMP) - Rizal Rizal; Sukron Mamun; MH Ainulyaqin; Kisanda Midisen; Sakum Sakum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of Islamic Boarding School-Owned Enterprises (BUMP) as a tool for the economic self-reliance of Islamic boarding schools requires professional business management that adheres to Sharia principles. However, optimizing the management and development of BUMP remains a challenge for many Islamic boarding schools. This study aims to analyze the role of Sharia management in the management and development of BUMP at the Attaqwa Putra Islamic Boarding School in Bekasi. The study employs a descriptive qualitative approach using interview and observation techniques. The results indicate that the role of Sharia management in operations is evident in how Sharia principles serve as the foundation for all business management activities, from planning, organizing, and execution to supervision. The implementation of these principles is evident in the management of various business units, such as cooperatives, canteens, printing and photocopying services, drinking water businesses, and laundry services. Additionally, Sharia management supports business development through strategic and innovative approaches that are gradual and sustainable, promotes entrepreneurship training and learning based on Islamic values, and utilizes simple technology in business operations. The application of Sharia management contributes to business sustainability and the strengthening of the pesantren’s economic independence.